Answer:
Explanation:
Array, A = (3, 5, 7, 2, 4, 3, 5, 8, 1)
By sorting array A = (1, 2, 3, 3, 4, 5, 5, 7, 8)
n = 9:
Let K, be the range of non-negative value
K = 8 - 1 = 7
Array, B = (7, 2, 4, 3, 5, 8, 1)
By sorting array B = (1, 2, 3, 4, 5, 8)
n = 7
K = 8 -1 = 7
a) Array, C after step 3 and 4 = (4, 3, 5, 8, 1)
By sorting array C = (1, 3, 4, 5, 8)
n = 5
Array, C after step 5 and 6 = (5, 8, 1)
By sorting array C = (1, 5, 8)
c) Arrays, B = (1, 2, 3, 4, 5, 8) and C = (1, 5, 8)
Both have the same K = 8 - 1 = 7